Upaya Meningkatkan Hasil Belajar IPA Menggunakan Model Pembelajaran Problem Based Learning (PBL) Di Kelas V SDN Buket Panyang - Zubaidah; Rosina Zahara (Indonesian Journal of Integrated Science and Learning, 2023)
The aim of this research is to determine the improvement in science learning outcomes using the Problem Based Learning (PBL) model in class V at SDN Buket Panyang. The research carried out was classroom action research (PTK). This PTK consists of 2 cycles with the research subjects being 21 class V students at SDN Buket Panyang. The data analysis technique was carried out descriptively. The research results obtained were that the student learning outcomes in the pre-cycle average score were 47.86 with student completeness 14.3%, in the first cycle the average student score was 66.43 with student completeness 61.9% , and in cycle II the average student score was 81.43 with student completeness 90.5%. Based on these results, it can be concluded that the use of the Problem Based Learning (PBL) model can improve student learning outcomes in Class V science subjects at SDN Buket Panyang.